Discovering the landscape of waqf financing: A bibliometric analysis - Abd Rahman, Nur Athirah; Abd Mutalib, Hasyeilla; Md Sabri, Sabiroh; Shafai, Nor Anis; Abdull Rahman, Nurul Labanihuda (Journal of Islamic, Social, Economics and Development, 2025)
This study presents an extensive bibliometric review of research publications on waqf financing using the Scopus database. Data analysis was conducted using Microsoft Excel, Open Refine, and VOSviewer. Since 2009, there has been a continuous growth in the number of research papers published on waqf financing. Malaysia emerged as the most productive country in terms of published waqf financing studies. Specifically, International Islamic University Malaysia ranked first as the most active institution in publishing important articles related to waqf financing research. The Journal of Islamic Accounting and Business Research stands out as the most renowned journal in this field. However, it should be noted that this research relies on the Scopus database, which may have certain limitations that can influence the results. The findings of this study provide important implications for improving the practice and reach of waqf financing globally.